How does health literacy associated to bio-behavioral and psycho-social outcomes among hemodialysis patients? A systematic review - Leila Zhianfar; Haidar Nadrian; Zeinab Javadivala; Sarisa Najafi; Shayesteh Shirzadi; Kamyar Pirehbabi; Ozra Honarpazhouh; Somayeh Azimi; Tahyebeh Shirvani; Sakineh Haj Ebrahimi; Devender Bhalla (BioSocial Health Journal)
Introduction: Although the life expectancy of kidney patients has increased due to hemodialysis (HD), the disease affects their lives in various ways. In this study, we systematically reviewed the relationships between health literacy (HL) and bio-behavioral and psycho-social outcomes in HD patients, to determine the necessary information needed for both micro- and macro-level health decision-making. Methods: We performed a comprehensive search for globally eligible studies (from 2000 to 2020) on PubMed, EMBASE, ProQuest, CINAHL Nursing, Cochrane Library and Google scholar. The quality assessment of the studies was performed using the standardized tool of the Joanna Briggs Institute (JBI). Results: Among 29 included studies, 23 and 6 articles were of medium and low quality, respectively, and no article was of high quality. In general, 7210 participants were included in these studies. In total, the lowest, highest and the average level of HL in all researches were reported to be 16%, 76.9% and 31.25% respectively. The findings showed a moderate level of evidence for the relationship of HL with self-care-associated outcomes, disease-related biomarkers, QOL, and perceived social support. Conclusion: Despite study heterogeneity and low quality, HL was found to be positively contributed to self-care behaviors, perceived social support and QOL of HD patients. HL seems to play an underpinning role in promoting HD patients’ QOL and its bio-behavioral and psychosocial determinants.